Development, Implementation, and Process Evaluation of a Theory-Based Nutrition Education Programme for Adults Living With HIV in Abeokuta, Nigeria - Bello, Temitope K.; Gericke, Gerda J.; MacIntyre, Una E. (Frontiers in Public Health, 2019)
Introduction: Healthy diets play a role in the management and care for adults living with HIV/AIDS (ALH). Appropriate nutrition education (NE) is necessary to equip ALH with relevant knowledge and skills for healthy eating. A needs assessment identified the need for a nutrition education programme (NEP) as part of the nutrition service for ALH in Abeokuta, Nigeria. The aim of this study was to design a theory-based NEP and to evaluate the implementation process among ALH attending selected federal and state hospitals in Abeokuta as out-patients. Materials and methods: An exploratory descriptive needs assessment in the qualitative and quantitative domains was conducted among a convenient sample of ALH (N = 243) at the selected hospitals. The quantitative needs assessment identified needs for improvement in the primary outcome (quality of life (QoL)) and the secondary outcomes (quality of dietary intake, nutrition knowledge, attitudes and practice (KAP), and anthropometric status). Participants’ perceptions of the NEP were obtained using an interviewer administered questionnaire among 70 ALH who attended the implementation of the NEP and process evaluation thereof at the intervention hospital. Results: The qualitative results identified a lack of knowledge on planning varied meals with limited resources. The identified needs, existing guidelines and literature were integrated with appropriate constructs of the Social Cognitive Theory (SCT) and the Health Belief Model (HBM) into the NEP. The NE manual, participant’s work book, flipcharts and the brochure were tailored to address the identified challenges. Discussion: The process evaluation showed that the NEP was implemented as planned and that the participants’ perceptions were positive. The use of the NE manual, participant’s work book, flipcharts and brochure demonstrated the practicality of incorporating behavioural theories in NE for ALH.